2009
DOI: 10.1016/j.tet.2008.10.033
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene-catalyzed oxidations

Abstract: N-Heterocyclic carbenes catalyze the oxidation of allylic and benzylic alcohols as well as saturated aldehydes to esters with manganese(IV) oxide in excellent yields. A variety of esters can be synthesized, including protected carboxylates. The oxidation proceeds under mild conditions, with low loadings of a simple triazolium salt pre-catalyst in the presence of base. Substrates containing potentially epimerizable centers are oxidized while preserving stereochemical integrity. The acyl triazolium intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 60 publications
4
44
0
2
Order By: Relevance
“…Recently, K. A. Scheidt and co-workers have reported that, in the carbene-catalyzed redox reaction of aldehydes and related processes, a transient benzylic alcohol intemediate should be accessible through addition of N-heterocyclic carbene to any aldehyde. [21] …”
Section: Resultsmentioning
confidence: 99%
“…Recently, K. A. Scheidt and co-workers have reported that, in the carbene-catalyzed redox reaction of aldehydes and related processes, a transient benzylic alcohol intemediate should be accessible through addition of N-heterocyclic carbene to any aldehyde. [21] …”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is consistent with numerous reports of NHC-catalyzed oxidative esterification of aldehydes with oxidants including azobenzene, 15 diphenoquinone, 16 and MnO 2 . 17 To test if our observations followed this proposal, we conducted the reaction under air in the presence of MeOH; to our surprise only the acid, rather than the expected ester was detected (entry 11). In contrast, the use of trans -azobenzene as the oxidant afforded cinnamic acid in the presence of water (entry 12) and methyl cinnamate in the presence of MeOH (entry 13).…”
mentioning
confidence: 90%
“…These observations are consistent with a number of reports of NHC-catalyzed oxidations of aldehydes with air or added stoichiometric oxidants. 7,8,1517 …”
mentioning
confidence: 99%
“…16 173.7, 136.9, 127.4, 126.2, 121.5, 118.6, 113.3, 109.1, 51.4, 34.9, 32.4, 20.4. Methyl 3-(1H-indol-3-yl)propanoate 17 1, 122.0, 121.4, 119.3, 118.6, 111.1, 51.1, 34.7, 20.6.…”
Section: General Procedures For the Synthesis Of 3-substituted Indolesmentioning
confidence: 99%